Analizando la Evolución de los E-servicios en los Principales Municipios Peruanos - Bohórquez López, Victor Wilfredo (2012)
The aim of this study is to analyze the evolution of development of e-services provided by major Peruvian municipalities, for which information is collected in late 2006 and mid 2012 in 43 municipalities of Lima. The results show that they have evolved positively in terms of access to information, as well as consultations and online payments, but there are many e-services to improve. On the side of citizen participation, municipalities are using social networks to be closer to citizens, giving them the option to interact in an environment that is more familiar to them.